Perception of stakeholders on School Management Awareness Creation on the Functionality of Complaint Mechanisms in Peculiar Situations in Nigeria - SHOWUNMI, A. A.; JIMOH, Taibat Bolanle (International Journal of Educational Management, 2025)
Complaint mechanisms in higher institutions of learning: In Nigeria is established to arbitrate, resolute conflicts and expedite justice among students, academic staff and non-academic staff. However, reports have shown that lack of creating awareness on the existence and functionality of complaint mechanisms especially in federal universities in the south-west, Nigeria can lead to negative outcomes. Previous studies on complaint in Nigerian universities concentrated largely on the causes, effects and use of leadership style and other conflict resolution approaches with little efforts on awareness of the existence and functionality of this complaint mechanism. In the light of this, the study intends to investigate school governance awareness creation and functionality of complaint mechanisms in peculiar situations in the South-West, Nigeria. Two research questions was raised and formulated. The study adopted descriptive survey research design. The population of the study consist of students, academic and non- teaching staff of the university. The sample of 1,260 respondents were drawn from the target population. The data collected were analysed using descriptive statistics. The study found out that academic staff members within the sampled universities perceived that their institutions' governance or management adequately create awareness of the mechanisms for handling disputes when they arise. The concluded that institution governance should make creation of awareness of complaint mechanism during peculiar situation is very significance to functionality of the complaint mechanism. It was recommended that more awareness should be created about the functionality of complaint mechanism The recommendations was also not be left out.